2004
DOI: 10.1097/01.aog.0000125148.82698.65
|View full text |Cite
|
Sign up to set email alerts
|

Management of Eisenmenger Syndrome in Pregnancy With Sildenafil and l-arginine

Abstract: The concomitant use of sildenafil and L-arginine for the management of pulmonary hypertension in pregnancy, combined with multidisciplinary care, permitted a good outcome for the mother and her infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 7 publications
(6 reference statements)
0
51
0
5
Order By: Relevance
“…Two of the 3 mothers and all 3 babies survived. One study shows that concomitant use of sildenafil and L-arginine for the management of pulmonary hypertension in pregnancy, combined with multidisciplinary care, permitted a good outcome for the mother and her infant [5]. Several studies done with heparin and vasodilators for the management of pregnancy with ES, revealed mixed response.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the 3 mothers and all 3 babies survived. One study shows that concomitant use of sildenafil and L-arginine for the management of pulmonary hypertension in pregnancy, combined with multidisciplinary care, permitted a good outcome for the mother and her infant [5]. Several studies done with heparin and vasodilators for the management of pregnancy with ES, revealed mixed response.…”
Section: Discussionmentioning
confidence: 99%
“…6 Currently, efficacy of sildenafil monotherapy in patients with PAH/CHD requires further studies. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Most authors reported positive outcomes with the use of epoprostenol [16][17][18][19][20]. Less data is available for nitric oxide [21], sildenafil [22,23], iloprost [24], and nebulized iloprost combined with epoprostenol [16,25]. A recent study has shown that 52% of pregnant women with CHD-PAH received PAH-specific therapy [7].…”
Section: Specific Therapies For Pulmonary Arterial Hypertension In Prmentioning
confidence: 99%